PEMANFAATAN SLUDGE LIMBAH KERTAS UNTUK PEMBUATAN KOMPOS DENGAN METODE WINDROW DAN CINA - Erliza Noor, Meika Syahbana Rusli, Muhammad Yani dan A. Halim dan N. Reza (Jurnal Teknologi Industri Pertanian, 2005)
ABSTRACTSludge generated from waste water treatment process of pulp and paper mill is a potential source of material to produce compost. It still contains a cellulose and mineral substances needed for composting. For composting in this experiment, the sludge was mixed with the rice husk in the ratio of 95:5, 85:15, and 75:25 (w/w) and added with Trichoderma viride in the concentration of 0.2% and 0.4% (v/w). The composting followed the China and Windrow methods. During composting the temperature reached 55oC after 12 days and C/N ratio decreased according to quadratic regression. In respect of the final C/N ratio obtained, composting using the China method showed a shorter time than by the Windrow method. The ratio of sludge and rice husk of  95:5 and concentration of Trichoderma viride 0.4% (w/v) resulted the best compost product for both methods. C/N ratio of 25 could be achieved in 34 days for China method and 39 days for Windrow method. The compost product fulfills the commercial compost standard. Key words : sludge, composting, windrow method, china method